2015
DOI: 10.1016/j.ijcard.2015.05.082
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of the subcutaneous implantable cardioverter defibrillator pre-implant screening tool

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Prior studies have suggested that “borderline passes” are more likely to lead to inappropriate shocks . Additional screening options that can be employed in borderline cases to potentially improve screening accuracy include the AST, exercise testing, and an algorithm‐based screening method . Even with these, however, clinical judgment on borderline cases should be used.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior studies have suggested that “borderline passes” are more likely to lead to inappropriate shocks . Additional screening options that can be employed in borderline cases to potentially improve screening accuracy include the AST, exercise testing, and an algorithm‐based screening method . Even with these, however, clinical judgment on borderline cases should be used.…”
Section: Resultsmentioning
confidence: 99%
“…Skin electrodes are placed to mimic the sensing configuration of the S‐ICD. In a study by Zeb et al., the sensitivity and specificity of the screening tool in normal individuals with structurally normal hearts using a standard ECG machine when compared to the S‐ICD sensing algorithm in a computer simulation was 95% and 79%, respectively …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensing algorithm for this system depends on the surface elecrtrocardiogram (ECG) morphology, specifically the R-and T-wave amplitudes, R/T and R/P ratios, QRS duration and QT interval. A pre-implant screening tool developed by the manufacturer (Boston Scientific Corp., Marlborough, MA, USA) is used in all patients under consideration for this device to select individuals with ECG morphology that offers appropriate signal configuration to satisfy the requirements of the subcutaneous ICD sensing algorithm, which are critical for an appropriate and effective delivery of the ICD implantation therapy [7] .…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the adequacy of the S-ICD, an ECG screening test was performed according to a program provided by Boston Scientific (Marlborough, MA, USA). 2 Each of three vectors was evaluated in the supine and standing positions. The secondary vector exclusively passed the screening test and the other two vectors failed in the left parasternal position.…”
Section: Case Reportmentioning
confidence: 99%